Cooling System Design for Cold Storage of Traditional Fishing Boat Using Insulation from Rice Husk - Muhammad Abidin; Alam Baheramsyah; Ede Mehta Wardhana (International Journal of Marine Engineering Innovation and Research, 2018)
Quality of fish is an important factor and determines the high selling price of fish in the market. In achieving that it will require proper handling in the process of cooling the fish before it is sold. To keep the freshness of the fish, fishermen usually use Styrofoam-based coolbox as its isolation. In this study modify coolbox using rice husk which serve as insulation on coolbox. This study aims to determine the effect of insulation using rice husk over time and temperature which will be compared with Styrofoam coolbox. Before the experiment, the first thing to do is to test the composition of rice husk with white cement. Where is the best composition to be used as insulation on coolbox. The tests are thermal conductivity, density, and flexural strength tests. From the test results obtained the best composition of rice husk and white cement is 1: 1 which has a thermal conductivity (0.746 W / mK) and density (0.32 gr / cm3) better than other compositions. In the experiments performed using 3 kg of wet ice it was found that in 24 hours cooling time, the rice husk coolbox had the lowest temperature of 13.5 ° C and the lowest Styrofoam coolbox temperature was 10.6 ° C.